An Efficient One-Pot Synthesis of 1, 5-Benzodiazepine Derivatives Catalyzed by TBAB under Mild Conditions - Mohammad A. Baseer; Asgar Jafar Khan (E-Journal of Chemistry)
2,3-Dihydro-1H-1,5-benzodiazepines were synthesized by reaction of o-phenylenediamine with ketones (acyclic / cyclic) under solvent free conditions in the presence of tetra butyl ammonium bromide (TBAB) in short reaction time with excellent yield.